2020
DOI: 10.1159/000506131
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Medical Radiation during Fetal Life, Childhood and Adolescence and Risk of Brain Tumor in Young Age: Results from The MOBI-Kids Case-Control Study

Abstract: Background: We explored the association between ionizing radiation (IR) from pre-natal and post-natal radio-diagnostic procedures and brain cancer risk within the MOBI-kids study. Methods: MOBI-kids is an international (Australia, Austria, Canada, France, Germany, Greece, India, Israel, Italy, Japan, Korea, New Zealand, Spain, The Netherlands) case-control study including 899 brain tumor (645 neuroepithelial) cases aged 10–24 years and 1,910 sex-, age-, country-matched controls. Medical radiological history wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…There are strong estimates of excess risk of cancer in childhood in the OSCC study of Bithell and Stiller ( Bithell and Stiller 1988 ) and of Bithell ( Bithell 1993 ) ( Table 2 , Supplementary Table S7 ), at doses that likely do not exceed 0.03 Gy, and borderline significant indications of excess risk for lympho-haematopoietic malignancies in the range of attained ages up to 61 years in the Southern Urals study of Schüz et al ( Schüz et al 2017 ) and for all thyroid nodules (mainly benign) at an attained age of 25–30 years in the Ukraine 131 I-exposed cohort of Hatch et al ( Hatch et al 2019 ) ( Table 3 , Supplementary Table S7 ). There are weaker indications of excess brain tumour risk in a case-control study of medical diagnostic exposures ( Pasqual et al 2020 ) ( Table 2 , Supplementary Table S7 ), for solid cancer in the in utero exposed Japanese atomic bomb survivors in the incidence study of Preston et al ( Preston et al 2008 ) at attained age of 12–55 years and in the mortality study of Sugiyama et al ( Sugiyama et al 2021 ) at attained age of 5–67 years ( Table 4 , Supplementary Table S7 ), and for lymphoma, leukaemia and solid cancer in the offspring of US radiologic technologists ( Johnson et al 2008 ) at attained age up to 20 years ( Table 3 , Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are strong estimates of excess risk of cancer in childhood in the OSCC study of Bithell and Stiller ( Bithell and Stiller 1988 ) and of Bithell ( Bithell 1993 ) ( Table 2 , Supplementary Table S7 ), at doses that likely do not exceed 0.03 Gy, and borderline significant indications of excess risk for lympho-haematopoietic malignancies in the range of attained ages up to 61 years in the Southern Urals study of Schüz et al ( Schüz et al 2017 ) and for all thyroid nodules (mainly benign) at an attained age of 25–30 years in the Ukraine 131 I-exposed cohort of Hatch et al ( Hatch et al 2019 ) ( Table 3 , Supplementary Table S7 ). There are weaker indications of excess brain tumour risk in a case-control study of medical diagnostic exposures ( Pasqual et al 2020 ) ( Table 2 , Supplementary Table S7 ), for solid cancer in the in utero exposed Japanese atomic bomb survivors in the incidence study of Preston et al ( Preston et al 2008 ) at attained age of 12–55 years and in the mortality study of Sugiyama et al ( Sugiyama et al 2021 ) at attained age of 5–67 years ( Table 4 , Supplementary Table S7 ), and for lymphoma, leukaemia and solid cancer in the offspring of US radiologic technologists ( Johnson et al 2008 ) at attained age up to 20 years ( Table 3 , Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…A 2-year lag time was applied to reduce the likelihood that the CT scan was done related to early symptoms of the brain tumour [11] leaving out the CT scans conducted within 2 years before the date of brain tumour diagnosis (Lag 2). 'Number of brain CT was the sum of CTs that include brain area, while 'Number of head CTs' was the sum of CTs conducted at the 1), based on a review of data published by Pasqual et al [12], who reported the radiation dose to the brain from conventional x-ray and CT. The literatures given time-age frame [13] and an estimation of brain dose [14] were used in a reference table . Mean dose values were estimated for new-borns and other age groups for head CTs and conventional x-rays of the head and neck, including whole body and unknown sites, excluding examinations conducted within the past 2 years.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…The advantages of using VRT in neurorehabilitation are the possibility of recovering a compromised function as a way to stimulate [ 36 ] neuronal reorganization and the induction of neuroplasticity (to maximize motor learning and neuroplasticity) and regain functions and abilities (even partially) by interacting with a virtual reality environment (VRE). The reference literature suggests that the alleged danger of the use of smartphones [ 48 , 49 ], in particular as a risk factor for the development of brain tumors, is in fact still debated and, even if the fear can be justified, we have no evidence that the danger is real [ 50 , 51 , 52 ].…”
Section: Brain Conditions and Diseases Associated With Smartphone In Childrenmentioning
confidence: 99%